2021
DOI: 10.1371/journal.pone.0253367
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting daily new infections, deaths and recovery cases due to COVID-19 in Pakistan by using Bayesian Dynamic Linear Models

Abstract: The COVID-19 has caused the deadliest pandemic around the globe, emerged from the city of Wuhan, China by the end of 2019 and affected all continents of the world, with severe health implications and as well as financial-damage. Pakistan is also amongst the top badly effected countries in terms of casualties and financial loss due to COVID-19. By 20th March, 2021, Pakistan reported 623,135 total confirmed cases and 13,799 deaths. A state space model called ‘Bayesian Dynamic Linear Model’ (BDLM) was used for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…There are various studies about COVID-19 forecasting in different region and countries of the world [ 9 , 15 , 16 , 19 , 26 – 28 ] including Pakistan, Canada, Germany, UK, France, Italy, Russia, Japan and Turkey. The studies of Aslam et al, [ 9 ], Khan et al [ 19 , 27 ] used time series models to forecast future’s scenario of COVID-19 in Pakistan. The results of Aslam et al [ 9 ] show increasing trend and suggested eightfold increase in recoveries and an increase of 2.7 times in new cases in the end of May 2020.…”
Section: Discussionmentioning
confidence: 99%
“…There are various studies about COVID-19 forecasting in different region and countries of the world [ 9 , 15 , 16 , 19 , 26 – 28 ] including Pakistan, Canada, Germany, UK, France, Italy, Russia, Japan and Turkey. The studies of Aslam et al, [ 9 ], Khan et al [ 19 , 27 ] used time series models to forecast future’s scenario of COVID-19 in Pakistan. The results of Aslam et al [ 9 ] show increasing trend and suggested eightfold increase in recoveries and an increase of 2.7 times in new cases in the end of May 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Based on observed river flow, the future’s forecast has been made by using BDLM. For further details about BDLM, I refer to 32 , 76 , 77 .…”
Section: Methodsmentioning
confidence: 99%
“…Khan et al [15] proposed that a flexible framework will help relevant departments formulate policies by predicting new infections of COVID-19 after 5 and 10 days. To observe the forecasting capability of our proposed β-Sutte indicator and βSA ensemble model further, the five days ahead prediction of the cumulative number of confirmed cases is also evaluated.…”
Section: Five Days Ahead Forecasting Of the Cumulative Number Of Conf...mentioning
confidence: 99%